2013
DOI: 10.1538/expanim.62.109
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of an Unidentified <i>Helicobacter</i> Species in Laboratory Mice and its Distribution in the Hepatobiliary System and Gastrointestinal Tract

Abstract: An unidentified Helicobacter species, strain MIT 01-6451, was frequently detected in mice obtained from domestic commercial and academic institutions in Japan. To partially characterize this strain, its distributions in the gastrointestinal tract and hepatobiliary system of mice were investigated. In gastrointestinal tissues, this strain was detected in all cecum, colon, and feces samples tested, whereas fewer mice were positive in the ileum, jejunum, and duodenum. Interestingly, strain MIT 01-6451 was also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 31 publications
(41 reference statements)
0
12
1
Order By: Relevance
“…At 6 weeks p.i, multifocal hepatitis was noticed in the infected mice which may indicate H.japonicum infection in the liver by translocating the intestinal barrier into hepatic tissues or alternatively, indirect effect of systemic cytokine response due to the primary intestinal infection (40). Even though we did not detect H.japonicum in the liver samples, in another study H.japonicum was identified in 33% gallbladder samples tested; however, they too did not detect the organism in liver samples (12).…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…At 6 weeks p.i, multifocal hepatitis was noticed in the infected mice which may indicate H.japonicum infection in the liver by translocating the intestinal barrier into hepatic tissues or alternatively, indirect effect of systemic cytokine response due to the primary intestinal infection (40). Even though we did not detect H.japonicum in the liver samples, in another study H.japonicum was identified in 33% gallbladder samples tested; however, they too did not detect the organism in liver samples (12).…”
Section: Discussioncontrasting
confidence: 67%
“…In a previous report, H.japonicum was abundantly detected in the colon and cecum of clinically normal mice, while lower amounts were present in the stomach, gallbladder and other regions of the intestinal tract (12). The lack of clinical signs in these mice is consistent with our analysis of H.japonicum-infected C57BL mice or C57BL mice infected with H.hepaticus, which also did not have clinical signs (8,12). Importantly, however, it has been reported that the severe combined immunodeficient mice infected with H.japonicum had lower birth rates when compared with Helicobacter spp.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations